BIOEFFICACY OF SOME INSECTICIDES AGAINST THE GREENHOUSE WHITEFLY TRIALEURODES VAPORARIORUM, WESTWOOD (HOMOPTERA: ALEYRODIDAE) ON TOMOTO - KUMAR, ARVIND; SINGH, RAJPAL (The Bioscan, 2014)
Laboratory bioassay of six insecticides namely, spiromesifen, cyantraniliprole, diafenthiuron, chlorfenapyr, buprofezin and oxy-demeton methyl and two botanicals azadirachtin (Neem Baan 1500 ppm) and aqeous dharek drupe extract against first instar nymphs of the greenhouse whitefly, Trialeurodes vaporariorum (Westwood) infesting tomato. These insecticides gave Respective nymphal mortality of these insecticides ranged from 30 to 96, 28 to 92, 22 to 92, 32 to 88, 26 to 86 and 28 to 88 per cent respectively. The range for azadirachtin and dharek drupe extract varied from 28 to 90 and 28 and 88 per cent. Their respective LC50 and LC90 values of the insecticides obtained were 9.80 and 13.48, 10.38 and 47.79, 18.91 and 85.60, 22.63 and 68.41, 31.45 and 168.65, 206.99 and 1148.15 ppm. Bio-pesticidal formulation, azadirachtin (Neem Baan) and dharek extract resulted in dosagedependent mortality with LC50 and LC90 values of 4.45 and 27.58 ppm and 2.84 and 8.60 per cent respectively. On the basis of LC50 and LC90 values, spiromesifen was found to be most effective followed by cyantrabniliprole. Neem formulation was found more toxic as compared to dharek drupe extract against this pest.